Perception And Comprehension Of Signage Wayfinding System In Hospitals For The Elderly In Guangzhou, China - Lujie, Deng (2024)
In the context of china's aging population, wayfinding in large and complex hospitals is one of the key challenges faced by the elderly.Currently, there exists a lack of research on the elderly’s perception and comprehension of hospital signage in china. This study aims to determine the actual requirements of hospital wayfinding signage among the elderly, and to provide recommendations for an age-friendly signage system. This study used mixed methods to investigate the elderly’s perception and comprehension of signage systems in three hospitals in guangzhou. The results of this study shows that most elderly have chosen to first ask others for directions, before using and following signage systems. And the elderly experience more difficulty reading and interpreting hospital signage. In signage, importantly helpful and valuable to the elderly are graphics, text, colour and updates to the signage system, because these elements directly affect the readability and understandability of the signage. Additionally, younger and more educated participants responded faster and more accurately. Moreover, the five cognitive features of symbols are positively correlated with comprehension levels; the accuracy of semantic depiction showed as the best predictor, followed by familiarity and concreteness, as these features are more likely to affect symbol comprehension and guessing ability. In conclusion, this study reveals the importance of considering the opinions and feedback of elderly users in designing hospital signage systems.